2019
DOI: 10.3390/antiox9010025
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antioxidants Beneficial Effects on Anion Exchange through Band 3 Protein in Human Erythrocytes

Abstract: Band 3 protein (B3p) exchanging Cl− and HCO3− through erythrocyte membranes is responsible for acid balance, ion distribution and gas exchange, thus accounting for homeostasis of both erythrocytes and entire organisms. Moreover, since B3p cross links with the cytoskeleton and the proteins underlying the erythrocyte membrane, its function also impacts cell shape and deformability, essential to adaptation of erythrocyte size to capillaries for pulmonary circulation. As growing attention has been directed toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 55 publications
(80 reference statements)
1
31
0
Order By: Relevance
“…The SDS-PAGE analysis revealed that cell treatment with HgCl 2 results in alterations in the membrane protein electrophoretic profile, particularly related to bands 3, 4.1 and 4.2. Band 3 protein (B3p) is the most abundant integral protein on the RBC membrane, endowed with specific anion exchange capabilities, being responsible for acid balance, ion distribution and gas exchange [ 52 , 53 ]. Furthermore, it is also involved in RBC mechanical and osmotic properties, such as maintenance of biconcave cell shape and deformability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SDS-PAGE analysis revealed that cell treatment with HgCl 2 results in alterations in the membrane protein electrophoretic profile, particularly related to bands 3, 4.1 and 4.2. Band 3 protein (B3p) is the most abundant integral protein on the RBC membrane, endowed with specific anion exchange capabilities, being responsible for acid balance, ion distribution and gas exchange [ 52 , 53 ]. Furthermore, it is also involved in RBC mechanical and osmotic properties, such as maintenance of biconcave cell shape and deformability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is also involved in RBC mechanical and osmotic properties, such as maintenance of biconcave cell shape and deformability. In particular, B3p is involved in specific protein–protein interactions, by connecting plasma membrane to the underlying cytoskeleton, through SH groups of specific Cys residues [ 53 ]. In this respect, Cys-201 and/or Cys-317, located at the cytoplasmic domain of B3p, are critical for ankyrin binding [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human erythrocytes are continuously exposed to oxidative molecules transported within the vascular system and possibly interacting with erythrocytes membrane, and are more susceptible to oxidative stress than other cells [ 26 ]. Oxidative damage has been demonstrated to decrease survival and rheological properties of human erythrocytes, affecting their homeostasis, which is strictly linked to Band 3 protein (B3p) function [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that Syk overactivation favors band 3 clusterization, allowing the release of erythroid microparticles and red cell membrane rearrangement. In addition, oxidation might also affect band 3 function as an anion exchanger [ 27 , 44 , 45 ]. Exogenous antioxidants, such as curcumin or melatonin, as well as the potentiation of endogenous cytoprotectors like PEP-Prx2, might prevent or limit band 3 oxidative damage, preserving band 3 structure and function [ 17 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%